USM IS SET ON INTENSIFYING COOPERATION FOR AN IMPACTFUL HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 22 October 2016 The ViceChancellor of Universiti Sains Malaysia (USM) Professor Datuk Dr. Asma Ismail described the budget presented by the Prime Minister as accommodating for higher education.